The association between non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio (NHHR) and sarcopenia: A cross-sectional study - Xiudeng Yang; Zheng Zhong (Experimental Gerontology)
Background: The non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio (NHHR) is a newly developed lipid parameter that's used to evaluate cardiovascular disease risk. However, its association with sarcopenia risk has not been explored before. Methods: Data on NHHR and sarcopenia were based on the secondary analysis of the years 2011–2018 of National Health and Nutrition Examination Survey (NHANES) dataset. NHHR was nature log-transformed (LnNHHR) to achieve a normal distribution. A multivariate logistic regression and a restricted cubic spline (RCS) model adjusted for associated factors were utilized to evaluate the correlation between NHHR and sarcopenia. Subgroup and sensitivity analyses were conducted to verify the robustness of the findings. Results: The study cohort comprised 7069 participants, of whom 6497 (91.91 %) were sarcopenia-free, and 572 (8.09 %) exhibited sarcopenia. A significant increase in NHHR was observed in the sarcopenia group compared to the non-sarcopenic group (P < 0.001). Multivariate logistic regression analysis revealed that sarcopenia was independently linked to NHHR [odds ratio (OR): 1.394, P = 0.007]. A linear relationship was identified between NHHR and sarcopenia risk (Pnon-linear = 0.108). Interaction analysis indicated that the relationship between NHHR and sarcopenia risk was not significantly modified by gender, sex, poverty income ratio, education, smoking status, or race. Conclusion: NHHR was significantly associated with an elevated risk of sarcopenia among U.S. adults. Further research is warranted to elucidate the underlying physiological mechanisms through which NHHR influences sarcopenia development.